Traumatic Experience and Delayed and Unconscious Responses in David Mitchell’s Ghostwritten - Mirsal Muhammed (International Journal of Practical and Pedagogical Issues in English Education)
This study analyzes the novel Ghostwritten by David Mitchell through the lens of trauma theory, a relatively new approach to literary analysis. Ghostwritten has been studied from a variety of perspectives, including postmodernism and globalization, but trauma theory has not yet been applied. The purpose of this study is to examine how the novel depicts trauma’s effects on individuals. Utilizing Cathy Caruth’s trauma theory, this study focuses on three central concepts: “delayed and unconscious responses”. The analysis indicates that the novel depicts trauma as an experience that defies representation and comprehension, with inadequate language conveying the full extent of such experiences. In addition, the novel emphasizes the paradox of testimony, in which trauma survivors are urged to speak about their experiences but find it difficult to do so in a meaningful and coherent manner. Thus, the findings of this study contribute to the ongoing dialogue about trauma and its depiction in literature.